Pengukuran Kinerja Bank Syariah Berdasarkan Maqashid Syariah Perspektif Abdul Majid Najjar - Adisasmita, Yusuf Hakim; Zaky, Achmad (Jurnal Perbankan Syariah, 2025)
In Indonesia, both conventional and Islamic banks continue to adopt conventional performance measurement approaches, which often fall short of aligning with Islamic sharia principles. Consequently, there is a pressing need for performance evaluation models specifically designed to reflect sharia principles in assessing Islamic banks. This study aims to evaluate and analyze the performance of Bank Muamalat Indonesia (BMI) over the period from 2020 to 2023 using the Maqashid Shariah Index (MSI) as developed from the perspective of Abdul Majid Najjar. Employing a single case study approach, the research is based on content analysis of secondary data obtained from BMI’s official website. The analysis reveals a decline in BMI's performance scores in 2021 and 2022 compared to its performance level in 2020. However, the performance score showed an upward trend in 2023. The decline in BMI’s performance in 2021 was primarily driven by a decrease in the Real Sector Investment Ratio. In 2022, the continued downturn in performance was influenced by a reduction in the Ecological Ratio. Conversely, the improvement in BMI’s performance in 2023 was largely attributed to an increase in the Ecological Ratio.